The Evolution of Bladder Augmentation: From Creating a Reservoir to Reconstituting an Organ - Jednak, Roman (Frontiers in Pediatrics, 2014)
Bladder augmentation was first described in 1899. The goal at the time was to establish the ideal method to create a simple capacious reservoir for the safe storage of urine. That simple idea has over the last 100 years grown into one of the most dynamic areas in Pediatric Urology. Creative minds and hands from individuals in multiple disciplines have led us from creating a reservoir to the threshold of recreating a functional organ. In this review, we look at the historical evolution of bladder augmentation and how it exponentially grew in scope from those initial descriptions of intestinocystoplasty to the work being reported today in the field of tissue engineering.